Group B Streptococcal Vaginal Colonization in the Third Trimester of Pregnancy - Kireçci, Ekrem; Özer, Ali; Arıkan, Deniz Cemgil; Gül, Mustafa (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: The presence of vaginal infections and Group B Streptococcus in the vaginal flora during pregnancy, bears importance because various resultant complications can be observed in pregnant women and their infants. The aim of our study is to determine the incidence of Group B streptococcal colonization among third trimester pregnant women who were admitted to the antenatal clinics of the Department of Gynecology and Obstetrics of the Medical Faculty of Kahramanmaras Sutcuimam University. STUDY DESIGN: In this study, vaginal smears were obtained from 97 of the 126 third trimester pregnancies within a period of two months and they were examined by microbiological methods. The specimens were cultivated in 5% sheep blood agar and incubated at 37 °C for 24 hours in an anaerobe environment. The streptococci isolated from the cultures were identified as Group B streptococcus by standard bacteriological methods and commercial latex agglutination kits. RESULTS: Mean age of the study group was 26.4±5.9 (range:18-44) years and mean gestational age was 36.7±3.3 (range: 27-42) weeks. Median gravida was 2 (range: 0-8), whereas median parity was 1 (range: 0-6). Amniotic membrane was ruptured in 14.4% of the pregnancies. 33.0% of the pregnancies had Group B streptococcal colonization. There was no significant difference with regard to age, gestational age, and gravida (p<0.05). 71.4% of the women with ruptured amniotic membrane and 26.5% of those with unruptured membrane were positive for Group B streptococcus; the difference between the groups was significant (p<0.05). CONCLUSION: Group B streptococcal colonization in our study group was found to be high. During and after pregnancy, in order to prevent infections and complications likely to form both in the mother and the infant, it is important to screen pathogenic factors by routine vaginal smears.